Gender Issues When Working with Men with Depression: A Novice Counsellor’s Perspective - Larson, Sarah E. M.; Anderson, Murray S. C. (Canadian Journal of Counselling and Psychotherapy, 2019)
Gender is an important cultural consideration for any counsellor, seasoned or novice. There is evidence to support the view that counsellors do not receive adequate training regarding gender issues and are ill-equipped to work with men and the unique issues that men face within North American culture. Depression is one of the most widespread mental health conditions worldwide, and cultural gender norms impact the symptoms of depression. It is important for novice counsellors to consider cultural influences on gender norms when working with male clients with depression. The purpose of this article is to outline the uniqueness of male depression, to show the effects of cultural gender norms and identity on the experience and perception of depression within clients and counsellors, and to provide recommendations for treatment for novice counsellors working with men with depression.